The overall experience of working in the retail marketing department under Communication Division of BRAC Bank Limited - Alam, Mahrufa Binte (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.